Evaluasi Manajemen Hubungan Masyarakat dan Sekolah (Studi Kasus di Madrasah Ibtidaiyah Miftahul Falah Purwodadi Pasuruan) - Novi Ariyanti; Muhammad Anggung Manumanoso Prasetyo (Institut Agama Islam Negeri Lhokseumawe, 2021)
The purpose of this research is to determine the Humas implementation model on the MIN Miftahul Falah Purwodadi Pasuruan. Descriptive qualitative survey research includes the principal, teacher, and educated labor are the informant sources. According to the study's findings, public relations evaluations include activities aimed at improving the quality of learners, public relations coaching, and supervision provided by both formal and informal principals. Parents and all school personnel conduct informal surveillance. Individual nonformal and formal evaluations are conducted in plenary or joint meetings at the mid and end of each semester, as well as at the end of the school year. The use of an operational approach is an important approach made in evaluation mechanisms. Less clear communication goals; transparent and professional communication channels; less supportive communication skills; less supportive follow-up; and less structured and continuous supervision are some of the most commonly encountered constraints. Substantive and relational outcomes are related in a positive way, implying the importance of effective public relations management practices.